EXAMINING THE IMPACT OF TELEVISION ADVERTISEMENTS ON CHILDREN'S BEHAVIOR (International Journal of Food and Nutritional Sciences, 2021)
Television is a potent medium that shapes the views of young people and encourages aconsumerist mentality via the use of vivid visuals and compelling stories. Commercials havea social impact because they add to kids' shared cultural experiences, which in turn shapetheir opinions, habits, and relationships.